Prophetical Law Paradigm: A Synthesis Of Thoughts Of Legal Philosophy Development - Catur Yunianto (Law Doctoral Program Universitas Muhammadiyah Surakarta, 2019)
ABSTRACT Purpose: This article aims to explain the philosophy dialectics of positivistic law and post positivistic law and elaborate on the dialectics of synthesis of thoughts of prophetic legal. Methodology: This research used a philosophical approach. The data were taken from secondary data using primary and secondary legal materials. The data were presented in an analytical descriptive manner, then analyzed in a normative juridical manner. Finding: The development of legal philosophy as an art of thought between empiricism, reality, rationality, and irrationality. Integration must be in presence to find the legal synthesis which is perceived capable of providing answers to the missing synthesis concerning the law. The basis of integration is conducted by retrieving the history and the thought schools development of natural philosophy, positivistic, non-systematic law and prophetic law. The synthesis of the thought schools of philosophical law is not only a reality built from the law itself but also the existence of extracurricular nullifications that can be synergized into near-perfect law. Benefit: The benefit of this research is to present the phenomena of various legal paradigms that develop simultaneously as a synthesis of legal development and as an answer to various problems of legal philosophy. The positivistic, non-systematic synthesis and the prophetic paradigm are the paths to near-perfect truth. Originality/Novelty: The prophetic paradigm developed within the framework of micro and macro realities are considered capable of providing answers to the reality of various criticisms that have existed so far. This prophetic paradigm has bonded micro, macro and transcendent realities which are divided into three categories; Theology, Humanity and Natural Sciences which are based on God’s verses on the Qur'an and Sunnah. Keyword: Philosophy of Law, Synthesis, Prophetic